2006
DOI: 10.1590/s1806-37132006000400004
|View full text |Cite
|
Sign up to set email alerts
|

Adesão ao tratamento de manutenção em asma (estudo ADERE)

Abstract: Objective: To determine the rate of compliance with preventive treatment of moderate and severe persistent asthma. Methods: Physicians at various medical centers across the country were invited to nominate patients for participation in the study. Inclusion criteria were being over the age of 12 and presenting moderate or severe persistent asthma. Participating patients received salmeterol/fluticasone 50/250 µg by dry powder inhaler for 90 days and were instructed to return the empty packages at the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
0
7
0
7
Order By: Relevance
“…Similar studies showed frequencies that vary from 30% to 70% [12]. In a national multicenter study that evaluated 131 people with asthma, Chatkin et al observed asthma therapy adherence in 51.9% of the patients [4]. …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar studies showed frequencies that vary from 30% to 70% [12]. In a national multicenter study that evaluated 131 people with asthma, Chatkin et al observed asthma therapy adherence in 51.9% of the patients [4]. …”
Section: Discussionmentioning
confidence: 98%
“…The authors also showed that the most severe asthma symptoms were associated with higher adherence to asthma therapy [4]. The reasons for patient's nonadherence are complex and are frequently related to patients themselves, health care professionals, the health care system, medications, and inhalation devices.…”
Section: Discussionmentioning
confidence: 99%
“…Cabe ressaltar que os odontopediatras de Itabira A maior causa levantada no estudo para a não adesão ao tratamento fonoaudiológico foi falta de tempo. Apesar do real excesso de atividades das quais as crianças nos dias atuais participam, e do fato de muitos pais não terem disponibilidade, em decorrência da jornada de trabalho, a gravidade da doença, o gênero e a restrição econômica são os fatores considerados na literatura para adesão/não adesão ao tratamento fonoaudiológico (13) . Entretanto, os pacientes podem omitir a verdadeira razão para não procurarem o tratamento indicado, uma vez que os próprios pesquisados relataram que aqueles com boas condições financeiras geralmente aderem à fonoterapia.…”
Section: Discussionunclassified
“…(1,4,21) The lack of asthma control in this subgroup of patients can be attributed to various factors: denial or underestimation of the disease by the patients; insufficient treatment for the severity of the disease; lack or incorrect use of asthma medications; limited access to health care services; presence of comorbidities; and factors inherent to the disease. (21)(22)(23)(24)(25)(26)(27)(28) Some authors have found that the use of inhaled corticoids is inversely proportional to the risk of death from asthma. (3) In the present study, we found that mortality was more common during the first 12 months of treatment for asthma, which suggests that the anti-inflammatory treatment period might have been cumulatively insufficient.…”
Section: Discussionmentioning
confidence: 99%